PHONETIC IMPLEMENTATION OF GEMINATES IN MALAYALAM NOUNS - John Local and Adrian P. Simpson
Malayalam employs gemination in syntactic and lexically distinctive roles. This paper presents an impressionistic and acoustic investigation of a subset of geminate consonants in Malayalam nouns. We show (a) that geminate sonorant consonants exhibit spectral differences as well as temporal ones and (b) that there are systematic spectral and temporal differences in vowels and consonants in nouns with and without geminates. Our findings suggest that gemination in Malayalam is best treated in terms of a long-domain phonological phenomenon having implications for articulatory and durational aspects of utterances extending over a number of syllables.